Analisa dan Perancangan Aplikasi Jasa Penitipan berbasis Android - Irfan Asidiq; Zaki Imaduddinz (LPPM STT Terpadu Nurul Fikri, 2017)
Entrusted culture is one of most culture in our live that we always do, even we plan it or not, from it we as a social human always depends to others, such as we want to buy drinks or foods, or many others thing that we need. This activities become an habit in our daily live, even it can not be apart with our daily activities, related with entrusted culture, there is other culture that being our basics need other than foods in our daily live, that is needs of internet. We can see not far in our environment today, there’s so many people from children to adults that made an internet being basics need than the daily foods. So, if we merge both of our culture that cannot be apart from our daily live and make it to an application, then it will be an interesting application. On this research, will be design an application for android mobile base that merging both of these two habits being something that interest. And results of this research hope fully will be a brand new business model in case of entrusted culture, and it can help to reduce big case of unemployment people today.